The accusative cases of nouns in the interpretation of (Uyun al-Tafasir by al-Fudala’ al-Samasir): The object as a model - عزيز, فريدون أحمد; البرزنجي, دلسوز جعفر (Sulaimani Journal for Humanities, 2019)
(Some of the interpreters - in addition to their duties in interpreting the Qur'anic verses - are linguists who have opinions, comments and comments on various grammatical topics. What the researcher can dig their grammatical opinions transmitted in their books. Which are basically encyclopedias full of linguistic material. It is a clear mirror that reflects the rules of Arabic grammar. The practical aspect of these rules. Because it contain the views of the grammarians with their discussion and the multiplicity of opinions and weighting between them. It is another view of grammatical books. This led the researcher to choose one of these interpreters and his book to study one of the grammar topics. He settled his opinion on Sheikh Shihab al-Din al-Siwasi (deceased 860AH), the author of the interpretation of (Oun Al-tafasser LelFuzalaa Al-samaseer), The reason for his choice is that he is a non-Arab Turkish interpreter, He lived in the fifteenth century AD, He lived in the country of Turk away from Arab countries and science centers, However, the researcher found that its interpretation is rich in grammatical material, Carrying discussions and opinions, worthy of research and study).